Role of Biopsychosocial Factors on the Risk of Pneumonia in Children Under-Five Years Old at Dr. Moewardi Hospital, Surakarta - Lestari, Nining; Salimo, Harsono; -, Suradi (Journal of Maternal and Child Health, 2017)
Background: It is estimated that the worldwide annual incidence of child pneumonia is approximately 156 million cases. Sixty-one million new cases occure in Southeast Asia with death rate of 3.1 million deaths per year. Prevalence of infant pneumonia in Indonesia is high at 1.8% in 2013 with mortality of 0.16% in 2015. This study aimed to determine the role of bio-psychosocial factors on the risk of pneumonia in children under-five years old.